Post-thrombotic syndrome and recurrent thromboembolism in patients with upper extremity deep vein thrombosis: A systematic review and meta-analysis. Issue 174 (February 2019) - Thiyagarajah, Kartiga; Ellingwood, Leah; Endres, Kaitlin; Hegazi, Aaron; Radford, James; Iansavitchene, Alla; Lazo-Langner, Alejandro
Abstract: Introduction: There is limited data on the occurrence of complications in patients with upper extremity deep vein thrombosis (UEDVT). Aims: We aimed to determine the frequency of post-thrombotic syndrome (PTS), thrombosis recurrence and major bleeding (MB) in patients with UEDVT. Material and methods: We conducted a systematic review of the literature including studies from 1970 onwards. We included observational studies, randomized trials, or cases series including >20 patients. We calculated pooled proportions using a random effects model. Subgroup analyses according to etiology and treatment modality were conducted. Results: A total of 62 studies comprising 3550 patients were included. The pooled proportions for PTS and recurrence were 19.4% (95% CI 11.3–27.6) and 7.5% (95% CI 4.1–10.9), respectively. With a mean follow up of 6 months, the proportion of PTS was higher in patients with primary (unprovoked) UEDVT compared to secondary, whereas recurrence was higher in secondary UEDVT. PTS was more frequent in patients treated with anticoagulation alone compared to thrombolysis or surgical decompression. The pooled proportion for MB was 5.0% (95% CI 0.3–9.7) after anticoagulation alone and 3.8% (95% CI: 2.4–5.8%) after thrombolysis and/or surgery. Conclusions: This study suggests that UEDVT is associated with significant rates of PTS and recurrence and its treatment has a relatively low risk of major bleeding. Differences exist depending on etiology and treatment modality. Highlights: We conducted a systematic review of upper extremity venous thrombosis complications. Post-thrombotic syndrome affects approximately 19% of patients. Recurrent thrombosis presents in approximately 7% of patients. Differences were noted in patients with unprovoked versus secondary events. High quality evidence in this area is lacking.